2010
DOI: 10.1007/s10563-010-9107-3
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous Solid Acid Catalysts

Abstract: Solid acids have been employed as one of the most important catalysts for chemical processes. However, relatively low surface area and small micropores of conventional solid acids have strongly limited their practical applications. This article systemically reviews the synthesis and catalysis performance of mesoporous solid acids including (1) mesoporous aluminosilicates, (2) mesoporous zeolites, (3) mesoporous sulfated zirconia, (4) mesoporous hybrid inorganic-organic materials, and (5) mesoporous resins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 178 publications
(209 reference statements)
0
12
0
Order By: Relevance
“…Much effort has been devoted to improve both the poor acidity and low hydrothermal stability of mesoporous molecular sieves over the past two decades [6][7][8][9]. It has been demonstrated that increasing the atomic order of the mesopore walls is an effective strategy to enhance both the acidity and hydrothermal stability [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Much effort has been devoted to improve both the poor acidity and low hydrothermal stability of mesoporous molecular sieves over the past two decades [6][7][8][9]. It has been demonstrated that increasing the atomic order of the mesopore walls is an effective strategy to enhance both the acidity and hydrothermal stability [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…It has uniform and adjustable mesoporous, high surface area, and large pore volume. However, the acidity and hydrothermal stability lower than conventional zeolites (Kovalchuk et al 2005;Taguchi and Schüth 2005;Bhattacharyya, Lelong, and Saboungi 2006;Chen, Meng, and Xiao 2011). Purely siliceous materials are poor in any catalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…Purely siliceous materials are poor in any catalytic activity. To obtain acidic sites, tetrahedrally coordinated Al species have been successfully introduced into the walls of MCM-41 (Kovalchuk et al 2005;Chen, Meng, and Xiao 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Many efforts have been dedicated to maintain ordered mesoporous structure of aluminosilicate assembling from zeolite seeds with improved acidity and hydrothermal stability [12][13][14] .The approach is based on surfactant directed assembly of zeolite seeds 55 containing zeolite building units that normally nucleate in the early stage during zeolites synthesis 15 . The most significant advantage of this method is that the Al species in the mesostructure are mostly located at zeolite-like sites, which exhibited strong acidic sites in the products 14 .…”
Section: Introductionmentioning
confidence: 99%
“…On the one 10 hand, the zeolite seeds improve the acidity and hydrothermal stability of supports; on the other hand, their high surface area improves cobalt dispersion at elevated metal loadings. Insights into the catalytic performance of these bifunctional catalysts would enable us to fine-tune their product selectivity, and make 15 these catalysts attractive for practical applications.…”
Section: Introductionmentioning
confidence: 99%